Effects of Different Preparation Methods on Protein Structure and Functional Properties of Konjac Fly Powder - Huaiye HE; Linghui KONG; Xun PEI; Wangting ZHOU; Muci WU; Rui ZHANG; Jingren HE (Shipin gongye ke-ji)
Konjac fly powder is the primary by-product of konjac refined flour processing, containing an abundance of proteins. In this study, three types of konjac fly powder proteins were prepared using alkaline extraction and acid precipitation, deep eutectic solvents (DESs)-dialysis and DESs-alcohol precipitation to enhance protein utilization. The impact of the preparation methods on the structural and functional properties of the proteins was investigated using SDS-PAGE, scanning electron microscopy, as well as UV and IR spectroscopy. The results revealed that the purity of the proteins prepared by the three methods ranged from 67.8% to 85.3%, mainly consisting of low molecular weight subunits in the range of 10~55 kDa. In comparison with the traditional alkaline extraction and acid precipitation, the molecular weight composition of the konjac proteins extracted by DESs remained unchanged, but there was a significant alteration in the relative content of the secondary structure. The TGA curves revealed that all three types of konjac proteins underwent thermal degradation at approximately 300 ℃, with the protein extracted through DESs-dialysis exhibiting the highest thermal stability at 316 ℃. Furthermore, the functional properties of proteins extracted by DESs were superior to those obtained by the alkaline extraction and acid precipitation, with the protein prepared through DESs-dialysis demonstrating better water and oil holding capacities as well as emulsifying properties. This study will provide valuable data to support the expanded application of konjac fly powder protein in the food industry.